2019
DOI: 10.3346/jkms.2019.34.e100
|View full text |Cite
|
Sign up to set email alerts
|

Nkx-2.5 Regulates MDR1 Expression via Its Upstream Promoter in Breast Cancer Cells

Abstract: Background Increased expression of MDR1 gene is one of the major mechanisms responsible for multidrug resistance in cancer cells. Two alternative promoters, upstream and downstream, are responsible for transcription of MDR1 gene in the human. However, the molecular mechanism regarding the transactivation of MDR1 upstream promoter (USP) has not been determined. Methods Dual-luciferase reporter gene assays were used to assess the effect of Nkx-2.5 on MDR1 USP activity usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…There have also been prior reports linking SNHG7 to chemoresistance, as in the study conducted by Chen et al ( 37 ) who observed the overexpression of this lncRNA in 26 DDP-resistant NSCLC tumors, with loss- and gain-of-function analyses confirming that higher SNHG7 expression levels promote DDP-resistance in these cancer cells. Mechanistically, SNHG7 silencing suppresses p-glycoprotein (MDR1) expression ( 38 ), ATP binding cassette subfamily G member 2 (BCRP) expression ( 39 ), and PI3K/AKT/mTOR pathway activation ( 40 ), all of which are related to chemoresistance. In this report, DDP-resistant NSCLC patient tumor tissues and cell lines exhibited marked SNHG7 upregulation, and the knockdown of this lncRNA confirmed its role as a promoter of NSCLC cell motility, proliferation, and resistance to DDP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There have also been prior reports linking SNHG7 to chemoresistance, as in the study conducted by Chen et al ( 37 ) who observed the overexpression of this lncRNA in 26 DDP-resistant NSCLC tumors, with loss- and gain-of-function analyses confirming that higher SNHG7 expression levels promote DDP-resistance in these cancer cells. Mechanistically, SNHG7 silencing suppresses p-glycoprotein (MDR1) expression ( 38 ), ATP binding cassette subfamily G member 2 (BCRP) expression ( 39 ), and PI3K/AKT/mTOR pathway activation ( 40 ), all of which are related to chemoresistance. In this report, DDP-resistant NSCLC patient tumor tissues and cell lines exhibited marked SNHG7 upregulation, and the knockdown of this lncRNA confirmed its role as a promoter of NSCLC cell motility, proliferation, and resistance to DDP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Cole et al в 1992 году открыли белок множественной лекарственной устойчивости (MDR1 или Pgp), который функционирует как аденозин-5-фосфатаза ATP-зависимая помпа для цитотоксических препаратов [18,19]. Он транспортирует отрицательно заряженные ионы, конъюгированные с молекулой глутатиона, обеспечивая резистентность к препаратам платины [20]. При отсутствии экспрессии в 100% случаев ответ на химиотерапию наблюдался в 96% случаев.…”
Section: Discussionunclassified
“…Among the subset of C2 pathways related to cancer, enriched pathways pointed to association of high BORG expression levels with high grade cancer phenotypes (Figure 4B,C). We showed that targets of a number of key carcinogenic transcription factors were enriched amongst genes upregulated in high BORG-expressing cells (Figure 4D), including those associated with metastasis and invasive phenotype (FOXD1, EVI1/MECOM, MEF2C), EMT (EVI1/MECOM, OCT1/POU2F1, MEF2A), brain metastasis (MEF2C), poor prognosis (FOXD1), and multi-drug resistance (NKX-2.5) [46][47][48][49][50][51][52][53] (Figure 4D,E,F). Interestingly, our previous work in murine models of breast cancer development and metastatic progression demonstrated robust acquisition of pro-metastatic and drug-resistance phenotypes following BORG overexpression 38,40,42 .…”
Section: Induction Of Invasive Signatures In High Borg-expressing Tnb...mentioning
confidence: 99%